Water Use in Rice Crop Cultivation in India: A Quantitative Assessment - Manish Debnath; Sumanta Chatterjee; A. K. Nayak; D. Chakraborty; H. Pathak (Agricultural Research, 2026)

Pharmacokinetics of praziquantel in rainbow trout, Oncorhynchus mykiss (Walbaum 1792) following a single dose oral administration - Sumanta Kumar Mallik; Richa Pathak; Krishna Kala; Prasanna Kumar Patil; Neetu Shahi; Ritesh Shantilal Tandel; Niladri Sekhar Chatterjee; Ranjit Kumar Nadella; Kishor Kunal (Veterinary Research Communications, 2025)

Multi-omics approaches: transforming the landscape of natural product isolation - Soumitra Sahana; Jyotirmay Sarkar; Sourav Mandal; Indranil Chatterjee; Susmita Dhar; Samaresh Datta; Sumanta Mondal (Functional & Integrative Genomics, 2025)

Correction to: Rapid urbanization leads to decline in forest cover and ecosystem services in India: insights from 10-m ESA Sentinel-2 land use land cover product - Sumanta Chatterjee; Smruthi Sagarika Mahapatra; Amaresh Kumar Nayak; Vikas Kumar Rai; Prakash Jha; Seyed Roohollah Mousavi (Theoretical and Applied Climatology, 2025)

Delineating soil fertility management zones using geostatistics and fuzzy clustering in semi-arid maize systems in India - Pandit Vaibhav Bhagwan; Theerthala Anjaiah; Chitteti Ravali; Makam Uma Devi; Tadikamalla Laxmi Neelima; Darshanoju Srinivasa Chary; Sumanta Chatterjee (Environmental Monitoring and Assessment, 2025)
This study quantified spatial variability in soil fertility attributes to delineate management zones (MZs) for site-specific nutrient management (SSNM) in a 4-ha maize field in northern Telangana, India. A total of 200 geo-referenced surface (0–15 cm) soil samples were analyzed for pH, electrical conductivity, organic carbon, and available nutrients (e.g., P, K, S, Fe, Mn, Zn, and Cu). Geostatistical analysis using ordinary kriging revealed that spherical models best were the best fit for describing the spatial structure of most parameters, with strong spatial dependence (nugget/sill < 0.25). Principal Component Analysis (PCA) reduced dimensionality, and fuzzy C-means clustering of the principal components delineated three distinct MZs, which were validated by ANOVA. Integration of MZs with targeted yield-based fertilizer recommendation equations enabled differential NPK application, resulting nutrient use efficiency gain equivalent to savings of up to 36 kg N, 39 kg P₂O₅ and 31 kg K₂O ha⁻ 1 in MZ -3. The maize yield increased from 7.27 t ha −1 under conventional farmer practices to 7.79 t ha −1 in MZ -1, 7.93 t ha −1 in MZ-2 and 8.02 t ha −1 in MZ -3 with corresponding benefit–cost ratio of 2.54, 2.60 and 2.65. MZ-3 consistently outperformed other zones in yield and economic return, demonstrating the agronomic and economic efficiency of site-specific nutrient management. This work demonstrates the potential of combining geostatistics and fuzzy clustering for optimal nutrient use efficiency and profitability in smallholder maize-based agroecosystems.

Rapid urbanization leads to decline in forest cover and ecosystem services in India: insights from 10-m ESA Sentinel-2 land use land cover product - Sumanta Chatterjee; Smruthi Sagarika Mahapatra; Amaresh Kumar Nayak; Vikas Kumar Rai; Prakash Jha; Seyed Roohollah Mousavi (Theoretical and Applied Climatology, 2025)
This research investigates short-term land use and land cover (LULC) changes and their impact on ecosystem services in eastern India from 2017 to 2022. It highlights how LULC alterations affect hydrodynamic variables and social factors. Using a globally established database, Ecosystem Service Values (ESV) were assessed through LULC analysis. The findings reveal a concerning decline in rainfall and vegetation health over the study period, suggesting potential climate change impacts. Notably, rainfall deviations in 2017 and 2022 were greater than the 30-year long-term average. Analysis using 10-m ESA Sentinel-2 remote sensing data indicated a 39.14% urban area expansion, while forest cover decreased by 9.76%, leading to an estimated loss of US$1,216 million in ESV. Conversely, ESV from croplands increased slightly by US$0.35 million, indicating possible improvements in irrigation infrastructure in Odisha. Wetland ESV also rose by 2.14% (US$8.81 million). The study highlights the critical role of LULC changes in influencing hydrodynamic variables such as rainfall and soil moisture, as well as social factors like urbanization. Understanding these interconnections is essential for effective land use planning and management. The findings can inform future policies, particularly in ecosystem service payments and rural livelihood improvements, ensuring sustainable development in the region. Graphical Abstract

Quantifying Climate Influence on Net Ecosystem Exchange in Lowland Tropical Rice: A Five-Year Eddy Covariance Study - Chinmaya Kumar Swain; Amaresh Kumar Nayak; Dibyendu Chatterjee; Suchismita Pattanaik; Vijayakumar Shanmugam; Sumanta Chatterjee; Pratap Bhattacharyya; Rahul Tripathi; Mohammad Shahid; Kiran Kumar Mohapatra; Abhijit Pradhan; Nihar Ranjan Singh (Agricultural Research, 2025)

Unraveling the potential of microbes in decomposition of organic matter and release of carbon in the ecosystem - Taqi Raza; Muhammad Farhan Qadir; Khuram Shehzad Khan; Neal S. Eash; Muhammad Yousuf; Sumanta Chatterjee; Rabia Manzoor; Sana ur Rehman; Joel Nathaniel Oetting (Journal of Environmental Management, 2023)

Fuzzy logic, geostatistics, and multiple linear models to evaluate irrigation metrics and their influencing factors in a drought-prone agricultural region - S.M. Rabbi Al Zihad; Abu Reza Md Towfiqul Islam; Md Abu Bakar Siddique; Md Yousuf Mia; Md Saiful Islam; Md Aminul Islam; A.B.M. Mainul Bari; Md Bodrud-Doza; Sobhy M. Yakout; Venkatramanan Senapathi; Sumanta Chatterjee (Environmental Research, 2023)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Actual evapotranspiration and crop coefficients for tropical lowland rice (Oryza sativa L.) in eastern India - Sumanta Chatterjee; Paul C. Stoy; Manish Debnath; Amaresh Kumar Nayak; Chinmaya Kumar Swain; Rahul Tripathi; Dibyendu Chatterjee; Smruthi Sagarika Mahapatra; Ammara Talib; Himanshu Pathak (Theoretical and Applied Climatology, 2021)

Mutations in SARS-CoV-2 viral RNA identified in Eastern India: Possible implications for the ongoing outbreak in India and impact on viral structure and host susceptibility - Arindam Maitra; Mamta Chawla Sarkar; Harsha Raheja; Nidhan K Biswas; Sohini Chakraborti; Animesh Kumar Singh; Shekhar Ghosh; Sumanta Sarkar; Subrata Patra; Rajiv Kumar Mondal; Trinath Ghosh; Ananya Chatterjee; et al. (Journal of Biosciences, 2020)

Partitioning of eddy covariance-measured net ecosystem exchange of CO2 in tropical lowland paddy - Sumanta Chatterjee; Chinmaya Kumar Swain; Amaresh Kumar Nayak; Dibyendu Chatterjee; Pratap Bhattacharyya; Smruthi Sagarika Mahapatra; Manish Debnath; Rahul Tripathi; Prabhat Kumar Guru; Biswaranjan Dhal (Paddy and Water Environment, 2020)

Water vapor flux in tropical lowland rice - Dibyendu Chatterjee; Amaresh Kumar Nayak; S. Vijayakumar; Manish Debnath; Sumanta Chatterjee; Chinmaya Kumar Swain; Priyanka Bihari; S. Mohanty; Rahul Tripathi; Mohammad Shahid; Anjani Kumar; H. Pathak (Environmental Monitoring and Assessment, 2019)

Characterization of land surface energy fluxes in a tropical lowland rice paddy - Dibyendu Chatterjee; Rahul Tripathi; Sumanta Chatterjee; Manish Debnath; Mohammad Shahid; Pratap Bhattacharyya; Chinmaya Kumar Swain; Rojalin Tripathy; Bimal K. Bhattacharya; Amaresh Kumar Nayak (Theoretical and Applied Climatology, 2019)

Greenhouse gas emissions and energy exchange in wet and dry season rice: eddy covariance-based approach - Chinmaya Kumar Swain; Amaresh Kumar Nayak; Pratap Bhattacharyya; Dibyendu Chatterjee; Sumanta Chatterjee; Rahul Tripathi; Nihar Ranjan Singh; B. Dhal (Environmental Monitoring and Assessment, 2018)